Histological Changes in the Pregnant, Lactating and Involuting Mammary Gland of the Guinea Pig - Nordin, W; Lee, C.S (1985)
The histological changes of mammary glands of guinea pigs during mid and late pregnancy, 1 day after parturition, peak lactation and 2, 3, 4, 8 and 12 days after weaning were studied. Rapid growth of the glandular tissue occurred towards late pregnancy and was completed by peak lactation. Plasma cells occurred in large numbers in the interalveolar connective tissue during the period between mid-pregnancy and lactation. Mammary involution was an autolytic process aided by the action of macrophages accompanied by shrunken alveoli and increased interalveolar connective tissue. This feature was evident at 3 days after weaning which began from the periphery of the glands. The number of macrophages were abundant in the connective tissue and alveolar and ductal lumina. By day 8, the alveoli were no longer recognisable and at 12 days after weaning only remnants of ductules and alveoli were present.